Knowledge about HIV/AIDS and implications of establishing partnerships among Hornet® users - Artur Acelino Francisco Luz Nunes Queiroz; Álvaro Francisco Lopes de Sousa; Matheus Costa Brandão Matos; Telma Maria Evangelista Araújo; Renata Karina Reis; Maria Eliete Batista Moura
ABSTRACT Objective: To evaluate the knowledge of men, who have sex with men who use geolocation-based dating software, about HIV/AIDS, and the implications of establishing partnerships. Method: Descriptive study with 30 Hornet® users. The statements generated had statistical treatment in the IRaMuTeQ software, analyzed through the Descending Hierarchical Classification. Results: The sexual frequency in the last 30 days was 2.9 partners, of which 2.1 were found by the application, of which 63.3% reported having sex without condoms. There were four classes: Knowledge about HIV/AIDS prevention measures; PrEP/truvada as a measure of HIV/AIDS prevention; Risky behaviors in relation to HIV infection; Establishment of sexual partnerships through applications. Conclusion: Hornet users have insufficient knowledge about HIV prevention measures, especially when discarding the male condom. The relationships established through the application are permeated by high individual vulnerability and behaviors that have potential exposure to the risk of HIV infection.